Disposable biosensor based on novel ternary Ru-PEI@PCN-333(Al) self-enhanced electrochemiluminescence system for on-site determination of caspase-3 activity - Luo, Weiwei; Chu, Hongyu; Wu, Xinzhao; Ma, Pinyi; Wu, Qiong; Song, Daqian (Talanta (Oxford), 2022)
The number of death due to cancer-related diseases each year is at the alarming level and is constantly growing. Tools that can effectively and conveniently detect cancer cell apoptosis can play a significant role in cancer research, cancer therapy, and other related industries. Herein, we fabricated, for the first time, an ultrasensitive, disposable, self-enhanced off-on electrochemiluminescence (ECL) biosensor based on ternary Ru-PEI@PCN-333(Al) system to determine caspase-3 activity, the biomarker of apoptosis. The biosensor had a low detection limit of 0.017 pg/mL and was able to enhance the ECL emission and stability. A solid-state (SS) ECL strategy was adopted to overcome the relatively weak ECL emission due to the long distance between electrochemiluminophore and electrode surface. The analysis requires only one incubation step, which can significantly reduce the operational complexity and time. The biosensor had higher sensitivity, and the off-on ECL mode was achieved using caspase-3 as a switch. The on-site and rapid detection capability of the biosensor was achieved by the introduction of disposable screen-printed electrodes (SPEs). This study lays a foundation for the development of more advanced, ingenious, portable and reliable ECL devices for biosensing not only caspase-3, but also other bioanalytes. [Display omitted] •We developed a disposable biosensor using the ECL technology to determination of caspase-3 activity.•The ternary Ru-PEI@PCN-333(Al) self-enhanced ECL system with excellent ECL performance was constructed for the first time.•The ECL biosensor had many advantages including on-site, rapid, disposable, low cost, simple batch production, and could effectively monitor the activity of caspase-3 during cell apoptosis.